Persepsi Petani Garam terhadap Inovasi Teknologi Pembuatan Garam Mikro di Kecamatan Dewantara Kabupaten Aceh Utara - Martina Nafla; Ekamaida Ekamaida (Journal of Agribusiness and Community Empowerment (JACE), 2020)
The purpose of this research is to uncover the Perception of Salt Farmers to ManufactureTechnology Innovation of micro salt in Dewantara District, Aceh Utara. The sample in this research,consisting of 41 salt farmers, weretaken by census. Analysis of the data was done using descriptive qualitative utilizing a Likert scale. The results of the study determines the perception of salt farmers based on the innovative characteristics of themanufacturing technology of micro salt in Dewantara  sub-district Aceh Utara district. The perception of relative advantage obtained a good category with an index value of 64.63percents. The perception of the complexity is the less complicated category with an index value of 63.41percents, perceptions of the technology can be observed as an unfavorable category with an index value of 60.12percents. Furthermore, the perception of the level of conformity of the category is relatively not good with an index value of 54.75percents.Finally, the perceptions of the technology can be tested unfavorable category with an index value of 54.63percents.